Imaging of Anatomical Variants of the Long Head Biceps Tendon - Fischetti, Michele; Romano, Alfonso Maria; Albano, Domenico; Di Salvatore, Mariano Giuseppe; Sconfienza, Luca Maria; Zappia, Marcello (Seminars in Musculoskeletal Radiology, 2023)
Anatomical variants of the long head of biceps (LHB) tendon are widely discussed in the literature. As one of the few intra-articular tendons, magnetic resonance arthroscopy can quickly evaluate the proximal part of LHB morphology. It provides good assessment of both intra-articular and extra-articular portions of the tendons. In-depth knowledge about imaging of the anatomical LHB variants discussed in this article is useful preoperatively for orthopaedists and also helps avoid potential diagnostic misinterpretations.
Keywords: long head biceps tendon; anatomical variants; magnetic resonance imaging; ultrasonography